Phytochemical and nutritional variation of country beans (Lablab purpureus) involving parents and hybrids: Phytochemical and Nutritional Variation of Country Beans (Lablab purpureus) (Journal of the Sylhet Agricultural University, 2025)
The fifteen country bean genotypes (Lablab purpureus) were grown to assess the nutritional status and phytochemical analysis. Morphological variation among the genotypes was also evaluated. The experiments were set up using one-way randomized complete block design with three replications. These 15 genotypes grown in winter season from August 2022 to January 2023 were IPSA Sheem -1(P1), Sikribi Sheem-1(P2), Sikribi Sheem-2(P3), BARI Sheem-1(P4), Golgadda Sheem (P5), and hybrids from P1× P2, P1× P3, P1× P4, P1× P5, P2× P3, P2× P4, P2× P5, P3× P4, P3× P5, and P4× P5. Nutritional parameters like crude protein (CP), antioxidant, dry matter (DM), and moisture content were studied. The highest CP (29.63%) was observed in IPSA Sheem-1 (P1). We found the highest antioxidant (Free radical scavenging activity of DPPH) in hybrid from P4× P5 (37.96%). P3× P5 hybrid had the highest DM (13.11%) and the highest moisture content (%) value was in P4× P5 (90.61%). In phytochemical analysis, the total phenolic content (TPC) and total flavonoid content (TFC) were studied. The highest TPC was (14.58 ug/mg) found in Golgadda Sheem (P5). P1× P4 hybrid had the highest TFC (4.25 ug/mg). Following morphological variation, the highest number (4.86) of seeds pod-1 was recorded in P1× P5. Based on nutrients IPSA Sheem -1(P1) was found to be more nutritious in the winter season compared to the other genotypes.J. Sylhet Agril. Univ. 11(2): 53-62, 2024